INSTITUT KESENIAN MAKASSAR - Rizal, Fahrul; Rahman, Sitti Aisyah; Rahayu, Irma (Nature: National Academic Journal of Architecture, 2014)
Development of the value of art and culture in Makassar fading , while the higher the education that is expected to help develop arts and cultural preservation . The number of art enthusiasts are having trouble finding a good college and adequate facilities in Makassar divert them out of the area for study. The main purpose of this paper in order to plan and merancangan Art Institute building located in Makassar, which can accommodate the needs of artists to distribute and develop creativity, the result of design art institute building is located in the subdistrict Tamalanrea location is adjusted with the direction of the located area Spatial education, it is expected that the center will be able to accommodate students in distributing and developing creativity and the provision of facilities that can accommodate the development and preservation of local culture and art according to user requirements in accordance with the planning and design standards that apply.